THE EFFECT OF PHET SIMULATION-BASED LEARNING ON STUDENTS’ CONCEPTUAL UNDERSTANDING IN PHYSICS - Ririn Arianti; Linda Sekar Utami; M. Isnaini (Jurnal Inovasi Fisika dan Edukasi, 2026)
PhET simulation-based learning represents an important aspect of physics education because it addresses persistent challenges related to students’ low conceptual understanding and the abstract nature of many physics topics. This issue highlights the need for further investigation into the effectiveness of interactive digital media in improving students’ conceptual mastery. This study aims to analyze the effect of PhET simulation-based learning on students’ conceptual understanding in physics. The research employed a quantitative approach with a quasi-experimental method, using a non-equivalent control group design. Data were collected through pre-test and post-test instruments to measure students’ conceptual understanding. The collected data were analyzed using descriptive statistics, N-gain analysis, and an independent sample t-test. The results indicate that students in the experimental class experienced a significant improvement, with mean scores increasing from 61.20 to 83.45 and an N-gain value of 0.70 (high category), while the control class showed an increase from 60.75 to 71.30 with an N-gain value of 0.35 (medium category). Furthermore, the independent sample t-test yielded a significance value of 0.000 < 0.05, confirming a statistically significant difference between the two groups. These findings demonstrate that PhET simulation-based learning effectively enhances students’ conceptual understanding by facilitating interactive visualization and promoting active learning. This study contributes significantly to the advancement of physics education at both national and international levels by offering an innovative instructional strategy grounded in digital technology integration. Additionally, the findings are expected to serve as a valuable reference for future research, particularly in the areas of technology-enhanced learning and conceptual understanding in physics, and to encourage more in-depth and applied studies in related fields.